Hubungan Status Nutrisi terhadap Hiperemesis Gravidarum pada Ibu Hamil di BPM Sarina Banyuasin Sumatera Selatan Tahun 2023 - Sarina Sarina; Ester Simanullang (Lembaga Pengembangan Kinerja Dosen, 2024)
Hyperemesis gravidarum is excessive nausea and vomiting in pregnant women to the point that it interferes with daily work because it generally becomes worse, due to dehydration. The aim of this research is to analyze the relationship between nutritional status and hyperemesis gravidarum in pregnant women at BPM Sarina Banyuasin in 2023. This research is quantitative. The population in this study were all pregnant women who experienced Hyperemesis Gravidarum, totaling 26 pregnant women. The sampling technique used is total sampling. The instrument used was a questionnaire and bivariate analysis using the Chi Square test. The conclusion was that there was a relationship between nutritional status and the incidence of hyperemesis gravidarum in pregnant women at BPM Sarina Banyuasin. Pregnant women with poor nutritional status will experience hyperemesis gravidarum 7.5 times compared to pregnant women with good nutritional status in the Singkil Community Health Center UPTD Work Area in 2024.